UJI DAYA TERIMA, KARAKTERISTIK FISIK, DAN MUTU GIZI MIE BASAH DENGAN SUBTITUSI TEPUNG KACANG MERAH (Phaseolus vulgaris L.) - Rizki Nurmalya Kardina; Andhini Eka S (UNUSA Press, 2017)
This study aims to determine whether substitution of wheat flour with red bean flour in the manufacture of wet noodles, resulting in wet noodles that are not only high in carbohydrates but also contain protein and natural antioxidant compounds. Addition of red bean flour with different percentage gives a real effect on water content, ash content, protein content, fat content, akrbohidrat content, and the elasticity of wet noodles. Parameters of nutrients analyzed have mean that is in accordance with SNI about nutrition content in wet noodles. The proportion of red bean flour in wet noodle making preferred by consumers based on favorite test is on P2 and P3 samples with red bean flour added 10% and 20%.